Забезпечення працездатності нечутливих до сил ваги некласичних автобалансирів - Невдаха, Ю. А.; Nevdakha, Y. (РВЛ КДТУ, 2003)
Дисертаційна робота присвячена розробці теоретичних принципів конструювання некласичних автобалансувальних пристроїв (АБП) нечутливих до сил ваги, призначених для більш точного зрівноваження вертикально розташованих роторів екстракторів, центрифуг, сепараторів, теоретичному й експериментальному визначенню умов працездатності нових пристроїв. Запропоновано усувати чутливість коригувальних вантажів (КВ) у некласичних АБП шляхом встановлення другого КВ і накладання на їх рухи в’язей. Виділені ознаки, комбінаціями яких створюються пристрої. Досліджені габаритні розміри, балансувальна ємність та інші технічні характеристики нових АБП. Теоретично й експериментально визначені умови працездатності пристроїв. Побудована модель ротора, який розташований вертикально, рухається плоскопаралельно, утримується ізотропними в’язкопружними опорами і зрівноважується запропонованим АБП. За допомогою теорії стійкості усталених рухів нелінійних автономних систем встановлена працездатність пристроїв на зарезонансних швидкостях обертання ротора. На універсальному стенді експериментально досліджена працездатність двох моделей АБП, зокрема при: різних режимах руху ротора; при зрівноваженні різних дисбалансів; дії збурень різного походження. Підтверджена працездатність пристроїв на зарезонансних швидкостях обертання ротора і переваги у роботі над АБП-прототипом. Розроблені додаткові рекомендації щодо поліпшення конструкції АБП: створювати нижній КВ меншої маси; збільшувати в’язкість сил внутрішнього опору; частково заповнювати порожнину АБП рідкою речовиною. The thesis is devoted to improving of a construction nonclassical automatic balancing devices (ABD) by a elimination of sensitivity of correcting masses (CM) to forces of weight, theoretical and experimental definition of conditions of serviceability of new devices. It is offered to eliminate sensitivity of CM in nonclassical ABD to forces of weight by installation of second CM and superposition by their movements of connections. The indications are chosen, which combinations form device by. The overall dimensions, balance capacity and other characteristics of the new ABD are investigated. Theoretically and experimentally conditions of serviceability of devices are certain. The model of a rotor is constructed which is located vertically, moves plain-parallel, is kept by isotropic viscous-elastic supports and statically is counterbalanced offered by ABD. With the help of theories of stability of the states motions of nonlinear autonomous systems and method of expansion of the roots of a polynomial on degrees of a small parameter the serviceability of devices is established on the speeds of rotation of a rotor, which is higher resonance. On the universal stand is experimentally investigated the serviceability of two models of ABD, including for: various modes of motions of a rotor; balancing various disbalances; operation of perturbations of a various origin. Is confirmed the serviceability of devices on rotation rate of a rotor, which higher that resonance one. The additional recommendations for improving a construction of ABD are produced: to execute lower CM by a smaller mass; to increase viscosity of forces of an internal resistance.
Maintenance of serviceability of not classical autobalancers which not sensitivity to the forces of weight
Keywords: автобалансир; балансування; віброзахист; дисбаланс; коригувальний вантаж; ротор; autobalancer; balancing; vibro-protection; disbalance; corrective mass; rotor